Transcriptomics reveals creatine regulation of ovarian development at low temperature in Chinese soft-shelled turtles (Pelodiscus sinensis) - Guoyin Zhang; Xi He; Yulong Li; Jiazhen Wu; Guoying Qian; Zhongfa Chen; Caiyan Li; Wei Wang (Aquaculture Reports)
Some economically important animals hibernate; however, their energy regulation during low-temperature fasting remain poorly understood. To investigate ovarian development in Chinese soft-shelled turtles (Pelodiscus sinensis) under low-temperature conditions, premature turtles were treated with creatine at concentrations of 50–400 mg/kg body weight. Ovarian follicle development, creatine kinase (CK) expression, and liver transcriptomics were analyzed. After 8 weeks of creatine treatment, ovarian follicle diameters and yolk granule accumulation increased significantly (P < 0.05), CK expression was significantly upregulated (P < 0.05), and ovarian lactic acid levels decreased significantly (P < 0.05). Transcriptome analysis identified 4355 differentially expressed genes in the liver. Creatine treatment significantly increased the expression of VTG, LEPR, LHR, FSHR, and CK-B genes, and genes in the adipocytokine signaling, oxidative phosphorylation, gonadotropin-releasing hormone (GnRH) signaling, and peroxisome proliferator–activated receptor signaling pathways were significantly upregulated. Creatine administration also enhanced leptin secretion from adipocytes, promoting ovarian development via the GnRH signaling pathway. This study provides a foundation for understanding energy metabolism in P. sinensis, offering insights to improve energy management and reproductive potential in hibernating animals under low-temperature conditions.